Mixing Bandt-Pompe and Lempel-Ziv approaches : another way to analyze the complexity of continuous-state sequences - Zozor, Steeve; Mateos, Diego M.; Lamberti, Pedro W. (2022)
Artículo finalmente publicado en. Zozor, S., Mateos, D. & Lamberti, P.W. Mixing Bandt-Pompe and Lempel-Ziv approaches: another way to analyze the complexity of continuous-state sequences. Eur. Phys. J. B 87, 107 (2014).